Etika Pergaulan Kaum Millenial: Studi Takhrij dan Syarah Hadis - Muhamad Rafli Alviansyah; Muhamad Yoga Firdaus; Tatang Zakaria; Dadang Kahmad (Gunung Djati Conference Series, 2022)
This study aims to analyze the hadith about millennial social ethics. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods by applying contemporary analysis. This study found that the quality status of the millennial social ethics hadith was considered valid. This hadith explains that Islamic morals or ethics can be said to be Islamic morality, namely morality rooted in the teachings of Allah and the Prophet. This study concludes that millennial youth always have a better understanding of hadith because Islamic morals appear in the form of community behaviour, so it can be used to indicate whether a person is a good Muslim or a bad Muslim.